2020
DOI: 10.3389/fsufs.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antimicrobial Activity Assessment of a Cauliflower By-Product Extract Against Salmonella Typhimurium

Abstract: The main objective of this work was to study the antimicrobial effect of a cauliflower by-product infusion into an affordable in vivo model (Caenorhabditis elegans). The infusion demonstrated some protective effect on non-infected and infected worms with Salmonella Typhimurium as indicated by higher survival percentile values (75, 50, 25, and 5% percentiles) as compared with those from worms unexposed to the infusion. The antimicrobial effect of the infusion was evaluated on Salmonella intestinal colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The lifespan assay is an index used to evaluate the bioactive potential (antiaging effect) of different compounds ( Ayyadevara et al, 2013 ; Jattujan et al, 2018 ; Chen et al, 2020 ; Ibáñez-Peinado et al, 2020 ). The cumulative survival curves of the nematode population fed with the different substrates can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lifespan assay is an index used to evaluate the bioactive potential (antiaging effect) of different compounds ( Ayyadevara et al, 2013 ; Jattujan et al, 2018 ; Chen et al, 2020 ; Ibáñez-Peinado et al, 2020 ). The cumulative survival curves of the nematode population fed with the different substrates can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Caenorhabditis elegans has been used very frequently as a model of pathogenesis, and in particular for infection by pathogenic microorganisms ( Balla and Troemel, 2013 ; Curt et al, 2014 ). In this sense, there are published studies in which the antimicrobial activity of a compound has been determined based on a higher survival of infected C. elegans when exposed to the antimicrobial compounds when compared with infected control nematodes (non-exposed to the antimicrobial compound) ( Sanz-Puig et al, 2017 ; Ibáñez-Peinado et al, 2020 ; Palacios-Gorba et al, 2020 ). In the present study, an independent set of experiments was specifically designed to study the Spirulina (treated and untreated by CP) antimicrobial activity against Salmonella enterica serovar Typhimurium when C. elegans worms were infected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature is a marvelous source of material for human throughout the history to cure their ailments and increase their fitness. Many studies revealed that plant extracts possess antibacterial potential [26,27]. Over the years, traditional healers have used water predominantly as solvent.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, people are looking for new natural antimicrobials to help in controlling those pathogenic microorganisms. The control of those microorganisms can be carried out by using natural antimicrobials as chitosan to be used in different foodstuffs reducing in this way the annual cases of illnesses transmitted by foods [32][33][34].…”
Section: Introductionmentioning
confidence: 99%